Draft Annual Plan 2004-2005 Administration of the Union Territory of Lakshadweep - Planning Commission (Planning Commission, 2004)
The objective of development planning, for enhancement of human well being as reflected in the social indicators on health, longevity, literacy and environmental sustainability as also expansion of production of goods and services and the consequent growth of per capita incomes; is followed in letter and spirit in the union territory of Lakshadweep as indicated in the statement of Monitorable Indicators as follows: Reduction of poverty ratio from 6.60% to 4% by 2007. Providing employment opportunities to 3000 by 2007 Achieving the target of all children in school by 2007 Reduction of gender gaps in literacy by 2005. Reduction in decadal rate of population growth between 2001 to 2011 from 17.19 to 8% Achieve 100% literacy by 2005.
Planning & Statistics Department, Secretariat, Lakshadweep, Kavaratti